Kidneys from elderly deceased donors-is 70 the new 60? - Echterdiek, Fabian Friedrich; Schwenger, Vedat; Döhler, Bernd; Latus, Jörg; Kitterer, Daniel; Heemann, Uwe; Süsal, Caner (Frontiers in immunology, 2019)
There is a growing shortage of kidney donors leading to extended transplant waiting times associated with increased mortality. To expand the donor pool, clinicians nowadays regularly accept organs from elderly donors, including those aged ≥70 years. There is only limited and conflicting data whether kidneys from these elderly donors allow for satisfactory allograft outcome rates. To asses this question, the 5-year death censored graft survival of 116,870 adult first deceased donor kidney allograft recipients that were transplanted at European centres between 1997 and 2016 and reported to the “Collaborative Transplant Study” were analysed using Kaplan-Meier analysis and country stratified Cox regression. The combinations of the two transplant periods 1997-2006 and 2007-2016 with the donor age categories 18-49, 50-59, 60-69, and ≥70 years were considered. From 1997-2006 to 2007-2016, the median donor age increased from 50 to 55 years and the proportion of kidneys from ≥60-year-old donors rose from 24.1% to 38.8%. At the same time, the proportion of kidneys from ≥70-year-old donors more than doubled (6.7% vs. 15.4%). Between 1997-2006 and 2007-2016, the 5-year graft survival improved in all donor age categories. During 2007-2016, the 5-year death censored graft survival of kidneys from ≥70-year-old donors was comparable to that of kidneys from 60-69-year-old donors during 1997-2006. This was true both for younger recipients (18-64 years) and older recipients (≥65 years). Among the younger recipients, 45-64-year-old recipients showed the best death censored graft survival rates for kidneys from old donors. In the country-stratified Cox regression analysis, compared to the reference of grafts from 18-49-year-old donors, the hazard ratio for grafts from ≥70-year-old donors during 2007-2016 was 1.92, exactly the same as the hazard ratio for grafts from 60-69-year-old donors during 1997-2006. Our analysis indicates that within only one further decade (1997-2006 vs. 2007-2016) the 5-year death censored graft survival of kidneys from ≥70-year old donors improved to the level of kidneys from 60-69-year-old donors in the previous decade.
Gesehen am 13.02.2020